2013
DOI: 10.3177/jnsv.59.479
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Deficiency and Cardiovascular Disease: Potential Mechanisms and Novel Perspectives

Abstract: Summary Interest in contemporary vitamin D research has been sparked in recent years, stemming from the identification of vitamin D receptors in virtually all cells as well as the enzymatic machinery necessary to produce its active form. Both epidemiological and invitro studies have linked vitamin D deficiency to enigmatic diseases including cardiovascular disease; however, a clear mechanistic link remains missing. This review highlights conclusions of observational studies, in-vitro experiments and randomized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…In fact, accumulating evidence suggests that 1,25(OH) 2 D, the bioactive molecule of vitamin D in the body, participates in the processes of immune regulation, apoptosis, and cellular proliferation and differentiation by directly or indirectly affecting expression of genes [5,7,8]. Thus, inadequate vitamin D could be a basic cause of many diseases, including cardiovascular disease [9], cancer [1012], and autoimmune diseases [7]. There is a need for individuals to learn their vitamin D status through testing, and public health research is needed to better understand the factors affecting vitamin D levels.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, accumulating evidence suggests that 1,25(OH) 2 D, the bioactive molecule of vitamin D in the body, participates in the processes of immune regulation, apoptosis, and cellular proliferation and differentiation by directly or indirectly affecting expression of genes [5,7,8]. Thus, inadequate vitamin D could be a basic cause of many diseases, including cardiovascular disease [9], cancer [1012], and autoimmune diseases [7]. There is a need for individuals to learn their vitamin D status through testing, and public health research is needed to better understand the factors affecting vitamin D levels.…”
Section: Introductionmentioning
confidence: 99%
“…Vit D is essential for optimal functioning of many organs and tissues (9). Vit D deficiency is correlated with coronary artery disease, heart failure, stroke, diabetes, hypertension, and endothelial dysfunction (10). NHANES III trial demonstrated negative association between serum 25(OH)D 3 levels and hypertriglyseridemia, diabetes, hypertension, and obesity (11).…”
Section: Discussionmentioning
confidence: 99%
“…Although the underlying pathophysiology is not fully understood yet, the role of vit-D in the inflammatory response, the renin-angiotensin-aldosterone system, and insulin resistance may help to reveal the pathogenesis [14]. Vitamin D deficiency has been associated with CAD, heart failure and stroke and identified as a risk factor for diabetes, hypertension, dyslipidemia and endothelial dysfunction [10]. The NHANES III (National Health and Nutrition Examination Surveys) study demonstrated an inverse relation between 25-hydroxyvitamin D 3 (25(OH)D 3 ) levels and hypertriglyceridemia, diabetes, hypertension and obesity [24].…”
Section: Discussionmentioning
confidence: 99%
“…They reported that there is higher myocardial infarction prevalence in patients with reduced vit-D levels than in patients with normal vit-D levels [9]. Subsequent studies showed that there is an association between vit-D deficiency and CAD, heart failure and stroke, and suggested that vit-D deficiency is a risk factor for diabetes, hypertension, dyslipidemia, endothelial dysfunction, subclinical atherosclerosis and atherosclerosis [1014]. The receptors of vit-D are located in vascular smooth muscle cells, and the role of vit-D in the inflammatory response, renin-angiotensin-aldosterone system and insulin resistance may help to explain the association between vit-D deficiency and CAD [14, 15].…”
Section: Introductionmentioning
confidence: 99%